Competency-Based Approach (CBA) and School Results in Physical Education and Sports in Secondary Schools in Côte D’ivoire - Spouse Binate, Dosso Namode Alice; Mamadou, Ganon (RA Journal of Applied Research, 2022)
As part of the reflection on the Ivorian educational system, this work aims at analysing the relationship between the Competency-Based Approach (CBA) and school results in Abobo's secondary schools in Physical and Sports Education (PSE). In fact, through the CBA, young people acquire various skills (knowledge and know-how) but also social skills (interpersonal skills) that give them value in social life. On the methodological level, a questionnaire was submitted to 79 (seventy-nine) teachers, including forty (40) public and thirty-nine (39) private teachers in the commune of Abobo. In addition, four (4) and two (2) resource persons were interviewed, including the head of the Pedagogy and Continuing Education Office (PCEO) in Abidjan. A mixed approach was used through the quantitative and qualitative method. The data collected was processed with MS EXCEL software, which was also used for the input and production of tables and graphs. The results of this study revealed that CBA is practised in Abobo secondary schools by about 50.60% of the teachers selected. More than 72% of the teachers interviewed have at least five (5) years of experience in teaching Physical and Sports Education (PSE). Most of them have therefore practised the OBA (objective-based approach) since the CBA, in its evolution through the teaching levels, entered the second cycle from 2015. The survey still reveals that these teachers have the required level of pedagogical skills or sufficient subject knowledge to teach effectively with this approach. Only 02.53% of the teachers surveyed may not have the recommended skills. However, it appears that CBA does improve students' academic performance in terms of knowledge, skills and also social or life skills, which are by nature skills for autonomy and conformity to social rules. Hence the use of the reference theory of social control, by Maurice Cusson (2015). It makes the school a situational and developmental prevention, effective in curbing deviance, delinquency and even criminality in young people.